Muscle and tendon adaptations to training: A functional perspective - Seynnes, O. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
The effectiveness and efficiency of ambulatory activities depends on the interaction between the architecture of lower limb muscles and the viscoelastic properties of connective tissue/ tendons to which they are connected. Training studies indicate that both parameters are altered following a period of exercise (1, 2), although the mechanisms underpinning some of these adaptations remain elusive. An increase in pennation angle is often associated with muscle hypertrophy following resistance training, and is assimilated to the necessary accommodation of additional in parallel sarcomeres. However, direct evidence of this assumption is currently missing. Furthermore, animal studies have shown that muscle fibre plasticity can occur lengthwise, via the addition of serial sarcomeres. Yet, reports of exercise-induced changes in fascicle length are conflicting, with some studies showing fascicular lengthening under certain training modalities (e.g. eccentric contractions), while others did not. Tendons display metabolic and structural adaptations following resistive training. In most cases, these changes are accompanied by an increase in stiffness and/or Young`s modulus. Scarce data also indicate a decrease in hysteresis. However, the time course and relative contribution of material and structural changes to mechanical behaviour differ considerably between studies, and information is lacking regarding adaptive patterns of tendinous tissue. In this presentation, I will review some aspects of training-induced changes in muscle and tendon and discuss their functional significance.